2006
DOI: 10.1182/blood-2006-09-047530
|View full text |Cite
|
Sign up to set email alerts
|

K-RasG12D expression induces hyperproliferation and aberrant signaling in primary hematopoietic stem/progenitor cells

Abstract: Defining how cancer-associated mutations perturb signaling networks in stem/ progenitor populations that are integral to tumor formation and maintenance is a fundamental problem with biologic and clinical implications. Point mutations in RAS genes contribute to many cancers, including myeloid malignancies. We investigated the effects of an oncogenic Kras G12D allele on phosphorylated signaling molecules in primary c-kit ؉ lin ؊/low hematopoietic stem/progenitor cells. Comparison of wild-type and Kras G12Dc-kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
109
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 44 publications
17
109
0
Order By: Relevance
“…34), Cbl, Cbl-b dKO bone marrow cells were hypersensitive to GM-CSF and able to form colonies even in the absence of exogenous cytokines. However, whereas both Kras G12D and Ptpn11 D61Y mutant mice show a reduction in the number of LSK cells in the bone marrow (35,36), this population is expanded in the bone marrow of Cbl-deficient (14) and Cbl/Cbl-b double-deficient mice (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…34), Cbl, Cbl-b dKO bone marrow cells were hypersensitive to GM-CSF and able to form colonies even in the absence of exogenous cytokines. However, whereas both Kras G12D and Ptpn11 D61Y mutant mice show a reduction in the number of LSK cells in the bone marrow (35,36), this population is expanded in the bone marrow of Cbl-deficient (14) and Cbl/Cbl-b double-deficient mice (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…It can be noted that, a higher percentage of Mx1-Cre, Kras G12D cells phosphorylated STAT5 in response to GM-CSF, but the magnitude and duration of STAT5 phosphorylation was similar in cells with both mutant and wild-type genotype. 8 We found that human myeloid progenitors bearing N-RAS mutation hyperphosphorylate STAT5 in terms of both magnitude of molecules and proportion of cells. Although our series is limited, the results show that human bone marrow CD34 þ / CD33 þ cells, but not CD34 þ /CD33À or CD34À/CD33 þ cells from JMML patients, represent the subset in which STAT5 hyperphosphorylation occurs in response to low doses of GM-CSF, and these observations were not reported earlier.…”
mentioning
confidence: 96%
“…More recently, Chou et al 7 published a novel TaqMan system for the absolute quantification of MRD with one common forward primer, a common probe and mutationspecific reverse primers. Scholl et al 8 additionally introduced methodological approaches for the rapid screening of NPM1 mutations by LightCycler assays based on the FRET principle, as well as MRD analyses of the most common mutations A and B with the LightCycler, using mutation-specific primers and SYBR Green.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model with an oncogenic Kras mutation (Kras G12D ) develops MPN, followed by T-ALL (20)(21)(22)(23). We evaluated the effect of Raptor deficiency on oncogenic Kras-driven hematopoiesis, particularly on the development of leukemia.…”
Section: Inactivation Of Mtorc1 Prevents Oncogenic Kras-induced T-allmentioning
confidence: 99%